Gender in Problem Based Learning: Curiosity Analysis, Problem Understanding, and Problem Solving Ability - Yusuf, Yusuf (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Research objectives This is analyze the effect of problem-based learning and gender on students’ curiosity, problem understanding, and problem-solving abilities. This research was conducted on two classes of Mataram Model X Madrasah Aliyah students who were selected using cluster random sampling technique. Student curiosity data was measured using a questionnaire instrument, while problem understanding and students’ problem solving abilities were measured using a question test instrument. Then, the data were analyzed by MANOVA at a significance level of 5%. The results showed that problem-based learning had a significant effect on curiosity and problem solving abilities, but did not have a significant effect on problem understanding. . The curiosity of male students is higher than that of female students, but the opposite occurs in the conventional group in classes taught with problem-based learning. The problem comprehension of male students was lower than that of female students in both study groups. problem solving of female students is higher than the group of male students. However, gender has no significant effect on curiousity, problem comprehension , and problem solving ability. The interaction of problem-based learning and gender has no significant effect on curiousity problem comprehension and problem solving abilities.